Deprivation of Multidimensional Poverty in Pekalongan City (Efficient: Indonesian Journal of Development Economics, 2022)
Poverty is a challenge in development that needs to be solved by each region. However, the calculation of poverty is still oriented to a one-dimensional approach, namely the monetary approach, even though the problem of poverty is multidimensional. Multidimensional poverty includes various deprivations experienced by poor people in their daily lives. This study aims to determine the condition of poverty in a multidimensional manner and the main deprivation of poverty in Pekalongan City. This study uses data from the 2019-2021 National Socio-Economic Survey (Susenas) and the Alkire-Foster multidimensional poverty measurement method, as well as 12 indicators in 3 dimensions (education, health, and living standards). The results show that multidimensional poverty for 3 years in Pekalongan City is always higher than the poverty measurement carried out by BPS. This study also found the priority scale of poverty alleviation assistance needed in Pekalongan City based on its main deprivation, namely the assistance program to overcome the years of schooling in the education dimension, nutritional adequacy in the health dimension and asset ownership in the standard of living dimension. Kemiskinan merupakan tantangan pembangunan yang perlu diselesaikan oleh setiap daerah. Namun penghitungan kemiskinan sampai saat ini masih berorientasi pada pendekatan satu dimensi yaitu pendekatan moneter padahal permasalahan kemiskinan bersifat multidimensi. Kemiskinan multidimensi mencakup berbagai deprivasi (kekurangan) yang dialami oleh orang miskin dalam kehidupan sehari-hari mereka. Penelitian ini bertujuan untuk mengetahui kondisi kemiskinan secara multidimensi dan deprovasi utama kemiskinan di Kota Pekalongan. Penelitian ini menggunakan data hasil Survei Sosial Ekonomi Nasional (Susenas) tahun 2019-2021 dan metode pengukuran kemiskinan multidimensi Alkire-Foster, serta 12 indikator dalam 3 dimensi (pendidikan, kesehatan, dan standar hidup). Hasil menunjukkan bahwa kemiskinan multidimensi selama 3 tahun di Kota Pekalongan selalu lebih tinggi dibandingkan pengukuran kemiskinan yang dilakukan oleh BPS. Penelitian ini juga menemukan skala prioritas bantuan pengentasan kemiskinan yang dibutuhkan di Kota Pekalongan berdasarkan deprivasi utamanya, yakni progman bantuan untuk mengatasi lama sekolah dalam dimensi pendidkan, kecukupan gizi dalam dimensi kesehatan dan kepemilikan aset dalam dimensi standar hidup.